Practical Approaches to the Use of Lenalidomide in Multiple Myeloma: A Canadian Consensus. (14th October 2012) - Reece, Donna; Kouroukis, C. Tom; LeBlanc, Richard; Sebag, Michael; Song, Kevin; Ashkenas, John
Abstract : In Canada, lenalidomide combined with dexamethasone (Len/Dex) is approved for use in relapsed or refractory multiple myeloma (RRMM). Our expert panel sought to provide an up-to-date practical guide on the use of lenalidomide in the managing RRMM within the Canadian clinical setting, including management of common adverse events (AEs). The panel concluded that safe, effective administration of Len/Dex treatment involves the following steps: (1) lenalidomide dose adjustment based on creatinine clearance and the extent of neutropenia or thrombocytopenia, (2) dexamethasone administered at 20–40 mg/week, and (3) continuation of treatment until disease progression or until toxicity persists despite dose reduction. Based on available evidence, the following precautions should reduce the risk of common Len/Dex AEs: (1) all patients treated with Len/Dex should receive thromboprophylaxis, (2) erythropoiesis-stimulating agents (ESAs) should be used cautiously, and (3) females of child-bearing potential and males in contact with such females must use multiple contraception methods. Finally, while Len/Dex can be administered irrespective of prior therapy and in all prognostic subsets, patients with chromosomal deletion 17(p13) have less favorable outcomes with all treatments, including Len/Dex. New directions for the use of lenalidomide in RRMM are also considered.